2014
DOI: 10.1002/pssb.201451217
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect in “reduced” dimensions: Thin films, ribbons, and microwires of Heusler alloys and related compounds

Abstract: Room temperature magnetic refrigeration is an energy saving and environmentally‐friendly technology, which has developed rapidly from a basic idea to prototype devices. The performance of magnetic refrigerators crucially depends on the magnetocaloric properties and the geometry of the employed refrigerants. Here we review the magnetocaloric properties of Heusler alloys and related compounds with a high surface to volume ratio such as films, ribbons, and microwires, and compare them with their bulk counterparts. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 156 publications
2
29
0
6
Order By: Relevance
“…The magnetocaloric effect (MCE) in various materials has been investigated extensively for potential magnetic materials that can be used as magnetic refrigerants in the last two decades [1][2][3][4][5][6][7][8][9][10]. Magnetic refrigeration technology based on MCE has many advantages, such as higher energy efficiency and more environmental friendly compare to the conventional gas compression/ expansion refrigeration technology.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetocaloric effect (MCE) in various materials has been investigated extensively for potential magnetic materials that can be used as magnetic refrigerants in the last two decades [1][2][3][4][5][6][7][8][9][10]. Magnetic refrigeration technology based on MCE has many advantages, such as higher energy efficiency and more environmental friendly compare to the conventional gas compression/ expansion refrigeration technology.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, review articles have been published on MSM/MMSM materials [13] and magnetocaloric materials [2,20,27]. Particular to MCE, research is also being carried out on using materials with reduced dimensions, such as thin films, ribbons and microwires [28]. Even though there is a vast amount of literature about multiferroic materials proportionate to the growing interest in them, a review of how the synthesis procedures and microstructures influence their magnetostructural properties would be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…But due to the expensive commercialization of Gd in magnetic cooling technology, over the past three decades various research groups around the world have focussed on developments of the magnetic refrigeration prototypes and finding new cheaper materials with better magnetocaloric properties. More detailed information about magnetic refrigeration prototypes and the latest achievements in this research field can be found in a series of recent review articles .…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, a large number of the intermetallic alloys and compounds including Gd–Si–Ge, Fe–Rh, La–Fe–(Si,Al), Mn–Ga–(C,N), Mn–Fe–(P,As), and Ni–Mn–(Ga, In, Sn, Sb) are also promising candidates in magnetic cooling technology . From this series of materials, the ferromagnetic Ni–Mn‐based Heusler alloys have been widely studied due to their potential applications as multifunctional materials possessing the magnetic shape memory effect, superelasticity, magnetic‐field‐induced strains, the direct and inverse MCE, the large magnetoresistance, Hall effect, etc.…”
Section: Introductionmentioning
confidence: 99%